Geriatric fracture centre vs usual care after proximal femur fracture in older patients: what are the benefits? Results of a large international prospective multicentre study. Issue 5 (10th May 2021) - Blauth, Michael; Joeris, Alexander; Rometsch, Elke; Espinoza-Rebmann, Kathrin; Wattanapanom, Pannida; Jarayabhand, Rahat; Poeze, Martijn; Wong, Merng K; Kwek, Ernest B. K.; Hegeman, Johannes H; Perez-Uribarri, Carlos; Guerado, Enrique; et al.
Abstract : Objective: The aim of this study was to determine the effect of treatment in geriatric fracture centres (GFC) on the incidence of major adverse events (MAEs) in patients with hip fractures compared with usual care centres (UCC). Secondary objectives included hospital-workflow and mobility-related outcomes. Design: Cohort study recruiting patients between June 2015 and January 2017. Follow-up was 1 year. Setting: International (six countries, three continents) multicentre study. Participants: 281 patients aged ≥70 with operatively treated proximal femur fractures. Interventions: Treatment in UCCs (n=139) or GFCs (n=142), that is, interdisciplinary treatment including regular geriatric consultation and daily physiotherapy. Outcome measures: Primary outcome was occurrence of prespecified MAEs, including delirium. Secondary outcomes included any other adverse events, time to surgery, time in acute ward, 1-year mortality, mobility, and quality of life. Results: Patients treated in GFCs (n=142) had a mean age of 81.9 (SD, 6.6) years versus 83.9 (SD 6.9) years in patients (n=139) treated in UCCs (p=0.013) and a higher mean Charlson Comorbidity Index of 2.0 (SD, 2.1) versus 1.2 (SD, 1.5) in UCCs (p=0.001). More patients in GFCs (28.2%) experienced an MAE during the first year after surgery compared with UCCs (7.9%) with an OR of 4.56 (95% CI 2.23 to 9.34, p<0.001). Analysing individual MAEs, this was significant for pneumonia (GFC: 9.2%; UCC: 2.9%; OR, 3.40 (95% CI 1.08 to 10.70), p=0.027) and delirium (GFC: 11.3%; UCC: 2.2%, OR, 5.76 (95% CI 1.64 to 20.23), p=0.002). Conclusions: Contrary to our study hypothesis, the rate of MAEs was higher in GFCs than in UCCs. Delirium was revealed as a main contributor. Most likely, this was based on improved detection rather than a truly elevated incidence, which we interpret as positive effect of geriatric comanagement. Trial registration number: ClinicalTrials.gov: NCT02297581 .